Implementation of the Pancasila Student Profile Project in Strengthening the Gotong Royong Dimension in Urban and Rural Elementary Schools: Exploring the Cooperation Subelement - Anggraita, Ryanjani Lila; Sumardjoko, Bambang; Desstya, Anatri; Prastiwi, Yeni (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study analyses the implementation of the Pancasila Student Profile Strengthening Project—an intracurricular initiative aimed at enhancing student competence and character—specifically focusing on the gotong‑royong (mutual cooperation) dimension in both urban and rural elementary schools in Jaten District, Karanganyar Regency. By engaging students in projects addressing local environmental issues, the research seeks to determine how effectively the collaboration subelement of cooperation is strengthened across different school contexts. Methodology: Employing a qualitative approach, the study involved 18 fifth‑grade students from rural schools and 28 from urban schools. Data were gathered through structured observation sheets, in‑depth interviews with participants and teachers, and review of project documentation. To ensure validity and reliability, the researchers applied triangulation—systematically reducing data, presenting findings, and drawing evidence‑based conclusions regarding each school’s project implementation stages of planning, execution, and evaluation. Results: Analysis reveals that both rural and urban schools successfully reinforced the gotong‑royong dimension’s cooperation subelement. In rural schools, students progressed to the “developing as expected” stage of collaboration skills. Urban students not only reached this stage but advanced further into “significantly developed” indicators, reflecting a higher level of cooperative competence compared to their rural peers. This demonstrates that context‑tailored project activities can differentially impact the depth of cooperative behaviors. Applications/Originality/Value: By comparing urban and rural implementations, this research provides actionable insights for educators and policymakers on tailoring the Pancasila Student Profile Strengthening Project to local needs. It underscores the importance of faithfully following the project’s planning–implementation–evaluation cycle and aligning activities with the specific Pancasila dimensions a school intends to bolster. These findings can guide teachers in both settings to design more effective, stage‑appropriate interventions that promote mutual cooperation and character development across diverse educational environments.